Social support and glycemic control in adult patients with type 2 diabetes mellitus - Chew, Boon How; Khoo, Ee Ming; Chia, Yook Chin (Sage Publications, 2015)
Introduction: The purpose of this study is to examine the prevalence of social support and its association with glycemic control in patients with type 2 diabetes mellitus (T2D) in an urban primary care center within an academic institution. Social support is important in the management of chronic diseases. However, its association with glycemic control has been controversial. Methods: This was part of a study examining religiosity in T2D patients. Nonsmoking patients with T2D for at least 3 years and aged 30 years and above were recruited. Social support was measured using The Social Support Survey-Medical Outcomes Study (SS), a self-administered questionnaire; the scores range from 19 to 95, and a high score indicates better social support. Glycemic control was measured using the 3 most recent glycosylated hemoglobin (HbA1c) levels within the past 3 years. Results: A total of 175 participants completed the SS survey (response rate 79.0%). The mean age was 62.7 (standard deviation [SD] = 10.8) years, and the mean duration of diabetes was 11.74 (SD = 6.7) years. The mean HbA1c level was 8.15 (SD = 1.44). The mean SS score was 68.1. The prevalence of high and low social support were 29.7% and 24.0 %, respectively. A significant correlation was found between SS score and number of social supporters (n = 167). No significant correlation was found between the self-reported number of social supporters or the SS score and the mean HbA1c level. Conclusions: Social support was not associated with glycemic control in adult patients with T2D in this primary care setting.